Nexus Among Debt, Profit, and Sustainability: Evidence from Indonesian Hotels - Agung, Chris Petra; Inawati, Wahdan Arum; Debby, Teresia (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
This study aims to analyze the relationship between: 1) liquidity and sustainability report (SR) disclosure; 2) SR disclosure and profitability; and 3) liquidity and profitability. This quantitative study is the first study to analyze the interaction among these three variables in the context of Indonesian hotel companies. Samples involved are companies that are listed in hotel, resort, and cruise industrial classification of Indonesia Stock Exchange (IDX) in 2021-2023 period. Data analysis is done using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The result shows that SR disclosure positively and significantly affects profitability. This finding supports the anticipation theory which states that there are benefits of anticipating action. Anticipation of sustainability would allow hotel companies to have lower costs related to future environmental-related regulations so that hotels can maintain more stable cash flow compared to companies who have not adapted the regulation at the current year. This finding also supports theory of corporate social responsibility (CSR) which views sustainability actions as “product” for customers and investors. These products exploit both existing and new markets and send signals of environmentally-aware perception to investors who would value the company higher. On the other hand, liquidity fails to positively affects both SR disclosure and profitability.